Readiness For Household Scale Waste Composting: Waste-Knowledge Management - Prasetyo, Agung; Anwar , Muhammad Fathul (JURNAL AGRIBISAINS, 2024)
The Surakarta City Government faces many obstacles in implementing the waste management system, especially household waste. These problems include waste management sites that are no longer able to accommodate waste (overload), low public awareness of clean and healthy living behavior (PHBS), weak sanitation management institutions and human resource capabilities. This research was conducted to determine the basic knowledge of the Surakarta City community regarding household waste management so that it can become a benchmark for waste handling in the future. The method used is descriptive and analytical and the respondents are 100 residents from five districts in Surakarta City. Data was collected through interviews with a questionnaire guide, observation, and recording, followed by analysis using descriptive statistics. The readiness level of 59.8% indicates that the people in Surakarta are ready to adapt to the conditions needed to achieve Knowledge Management readiness in household-scale composting. Counseling to improve waste processing skills for Surakarta residents can be carried out as an option to reduce waste from the main source of waste engagement.